2018
DOI: 10.1111/ecoj.12567
|View full text |Cite
|
Sign up to set email alerts
|

Looking Down the Barrel of a Loaded Gun: The Effect of Mandatory Handgun Purchase Delays on Homicide and Suicide

Abstract: We exploit within-state variation across time in both the existence and length of statutory delaysboth explicit wait periods and delays created by licensing requirementsbetween the purchase and delivery of a firearm to examine the effect of purchase delays on homicides and suicides. We find that the existence of a purchase delay reduces firearm-related suicides by between 2% and 5% with no statistically significant increase in non-firearm suicides. Purchase delays are not associated with statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…A substantial literature finds that more restrictive state firearm regulations are associated with fewer firearm deaths in those states, 2,3,8,30,31 although the associations can differ for homicides and suicides. 2,3,32 However, firearm control policies vary greatly across states, 33 and guns can cross state borders with relative ease-a relatively new but growing body of literature is starting to explore whether there is a neighbor effect, whereby weaker regulations in neighboring states dilute the impact of strict in-state regulations. This study analyzed Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial literature finds that more restrictive state firearm regulations are associated with fewer firearm deaths in those states, 2,3,8,30,31 although the associations can differ for homicides and suicides. 2,3,32 However, firearm control policies vary greatly across states, 33 and guns can cross state borders with relative ease-a relatively new but growing body of literature is starting to explore whether there is a neighbor effect, whereby weaker regulations in neighboring states dilute the impact of strict in-state regulations. This study analyzed Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…23 Some researchers have used changes in laws surrounding gun ownership to examine the gun availability/suicide link, but the evidence is mixed. Using a panel of states, Edwards et al (2018) found mandatory delays in handgun purchases reduce suicides. In contrast, Duggan, Hjalmorsson, and Jacob (2011) found that gun shows had no short-term impact on suicide rates in nearby areas.…”
Section: Gun Suicides As a Proxy For Gun Possessionmentioning
confidence: 99%
“…Recent studies, for example, continue to find evidence of a positive correlation between gun availability and suicide rates. [12] Given the life and academic stresses associated with the college/university experience, the greater availability of handguns could have the unintended consequence of triggering a spike in suicide rates as handguns become more commonplace on college campuses. In this sense, the decision of policymakers across multiple states to enact policies that align with preferences not shared by the vast majority of those most affected, and despite the potential harms such policies could entail, is an area that requires more intensive academic and public scrutiny.…”
Section: Disconnect With Public Opinion and Health Effectsmentioning
confidence: 99%